2013
DOI: 10.1016/j.juro.2013.02.103
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Mediated Inhibitory Neurotransmission to the Pig Bladder Neck: Role of K ATP Channels, Sensory Nerves and Calcium Signaling

Abstract: H2S produces pig bladder neck relaxation via activation of adenosine 5'-triphosphate dependent K(+) channel and by smooth muscle intracellular Ca(2+) desensitization dependent mechanisms. H2S also promotes the release of sensory neuropeptides and cyclooxygenase-1 pathway derived prostanoids from capsaicin sensitive primary afferents via transient receptor potential A1, transient receptor potential vanilloid 1 and/or related ion channel activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 30 publications
1
28
1
1
Order By: Relevance
“…Vascular tone is dependent on the relative activities of MLC kinase and MLCP, where activation of MLC kinase or inhibition of MLCP can increase phosphorylation of MLC and thereby initiate vascular smooth muscle contraction (Somlyo and Somlyo, 2003). Inhibition of MLCP, but not Rho-kinase, reduced the H 2 S-induced relaxation of mouse gastrointestinal smooth muscle (Dhaese and Lefebvre, 2009); in the pig bladder, H 2 S lowered tension without changing the calcium concentration (Fernandes et al, 2013). In our study, H 2 S initially evoked vasodilation while the intracellular calcium levels increased or were maintained at the same level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular tone is dependent on the relative activities of MLC kinase and MLCP, where activation of MLC kinase or inhibition of MLCP can increase phosphorylation of MLC and thereby initiate vascular smooth muscle contraction (Somlyo and Somlyo, 2003). Inhibition of MLCP, but not Rho-kinase, reduced the H 2 S-induced relaxation of mouse gastrointestinal smooth muscle (Dhaese and Lefebvre, 2009); in the pig bladder, H 2 S lowered tension without changing the calcium concentration (Fernandes et al, 2013). In our study, H 2 S initially evoked vasodilation while the intracellular calcium levels increased or were maintained at the same level.…”
Section: Discussionmentioning
confidence: 99%
“…A number of other mechanisms underlying H 2 S-induced vasorelaxation have been suggested, including involvement of NO (Zhong et al, 2003;Cheang et al, 2010), release of calcitonin gene-related peptide from nerve-endings due to activation of transient receptor potential ankyrin-1 channels (Fernandes et al, 2013;White et al, 2013), and changes in intracellular pH through an effect on a 4.4-diisothiocyano-2.2ʹ-stilbenedisulfonic acid-sensitive Cl 2 /HCO 3 -exchanger (Lee et al, 2007;Kiss et al, 2008). Opening of potassium (K) channels leads to hyperpolarization and closing of voltagedependent Ca 21 -channels, decreasing the intracellular calcium concentration ([Ca 21 ] i ), followed by vasodilation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that in DSM, H 2 S induces concentrationdependent contraction by stimulating tachykinins release and activation of NK 1 and NK 2 receptors (37). In the ureter and bladder neck, it is believed that H 2 S induces smooth muscle relaxation by stimulating capsaicin-sensitive primary afferents, which release inhibitory neuropeptides (8,10). Besides these few recent reports, there is no information about the role of H 2 S in the cholinergic neurotransmission or BK channel activity in DSM.…”
mentioning
confidence: 99%
“…A similar smooth muscle relaxant effect of GYY4137 has now been described in a range of tissues including human airway smooth muscle cells via opening of sarcolemma K ATP channels (Fitzgerald et al, 2014), mouse intrapulmonary airways by an effect on intracellular calcium release (Castro-Piedras & Perez-Zoghbi, 2013), pig bladder neck tissues again by opening K ATP channels (Fernandes et al, 2013), pregnant rat myometrial smooth muscle cells (Robinson & Wray, 2012) and in the bovine ciliary artery (Chitnis et al, 2013). Intriguingly, GYY4137 can occasionally, and in defined conditions, exert the opposite effect on blood vessels.…”
Section: Effect Of Gyy4137 On Nonvascular Smooth Musclementioning
confidence: 55%